Peroxisomal beta-oxidation enzyme proteins in adrenoleukodystrophy: distinction between X-linked adrenoleukodystrophy and neonatal adrenoleukodystrophy. - Chen, W W (1987)
Very long chain fatty acids, which accumulate in plasma and tissues in X-linked adrenoleukodystrophy (ALD), neonatal ALD, and the Zellweger cerebrohepatorenal syndrome, are degraded by the peroxisomal beta-oxidation pathway, consisting of acyl-CoA oxidase, the bifunctional enoyl-CoA hydratase/3-hydroxyacyl-CoA dehydrogenase, and beta-ketothiolase. A marked deficiency of all three enzyme proteins was reported in livers from patients with the Zellweger syndrome, a disorder in which peroxisomes are decreased or absent. Peroxisomes are not as markedly decreased in neonatal ALD and appear normal in X-linked ALD. Immunoblot analysis of the peroxisomal beta-oxidation enzymes revealed an almost complete lack of the bifunctional enzyme in neonatal ALD liver, similar to the finding in Zellweger tissue. In contrast, acyl-CoA oxidase and beta-ketothiolase were present in neonatal ALD liver, although the thiolase appeared to be in precursor form (2-3 kDa larger than the mature enzyme) in neonatal ALD. Unlike either neonatal ALD or Zellweger syndrome, all three peroxisomal beta-oxidation enzymes were present in X-linked ALD liver. Despite the absence in neonatal ALD liver of bifunctional enzyme protein, its mRNA was detected by RNA blot analysis in fibroblasts from these patients. These observations suggest that lack of bifunctional enzyme protein in neonatal ALD results from either abnormal translation of the mRNA or degradation of the enzyme prior to its entry into peroxisomes.